F-18 FDG-PET-CT in the Diagnostic of a Late Medullary Thyroid Carcinoma Recurrence in a Patient with Follicular-Papillary Thyroid Cancer - Doina Piciu; Andra Piciu (Case Reports in Endocrinology)
Mixed medullary and follicular or papillary carcinoma of thyroid is an extremely rare tumor, characterized by coexistence of morphological and immunohistochemical features of both medullary carcinoma and follicular (or papillary) carcinoma. This case report describes for the first time in the indexed database a late recurrence of a medullary thyroid carcinoma initially diagnosed as follicular-papillary form, treated and monitored accordingly. After 14 years, a superior mediastinum tumor was discovered incidentally at a thorax computer tomography. The whole-body I-131 scan was negative and F-18 FDG-PET-CT showed glucose avidity of the tumor. The patient was operated on and the histology revealed medullary thyroid carcinoma. If there are no possibilities to have routinely extensive immunohistologic profiles, it is recommended to check the serum calcitonin, at least in any patient with confirmed thyroid carcinoma.